Overview of Dengue and Zika virus similarity, what can we learn from the Saudi experience with dengue fever? - Alshammari, Sulaiman A.; Alamri, Yousif S.; Rabhan, Fatimah S.; Alabdullah, Aljoharah A.; Alsanie, Noura S.; Almarshad, Fatma A.; Alhaqbani, Amal N. (International Journal of Health Sciences, 2018)
There is high public health alert in the Kingdom of Saudi Arabia concerning Zika virus infection. So far there is no reported outbreak. So are we at risk of this disease? Reviewing the literature of recent outbreaks of other infectious diseases in Saudi Arabia may clarify the situation. It is evident that there is some similarity between zika and dengue regarding vector (Aedes aegypti) which is available in the Kingdom of Saudi Arabia. Also, they have similar transmission process and the required environment for infection. It seems that the Kingdom has learned from previous outbreaks, so they are well prepared to face such challenges. The Saudi ministry of health built the command and control center to deal with the pandemic flues. Also, they are trying to create a center for disease control, and they are recruiting local and international experts in monitoring the emerging infections.